Penyuluhan Hukum Prosedur Mediasi di Pengadilan Kepada Masyarakat Kelurahan Kampung Melayu Kecamatan Sukajadi Kota Pekanbaru - Afrita, Indra; Dewi, Sandra; Andrew Shandy Utama (Jurnal ABDIMAS STMIK Dharmapala, 2021)
Problems partners in the Community Service activities are the lack of public knowledge Kelurahan Kampung Melayu Kecamatan Sukajadi Kota Pekanbaru on mediation procedure in court. The solution offered in community service activities are increased knowledge of Kelurahan Kampung Melayu Kecamatan Sukajadi Kota Pekanbaru on mediation procedure in court. Method of implementation of Community Service is using lectures, dialogues and discussions in the framework of legal counseling on increased knowledge of Kelurahan Kampung Melayu Kecamatan Sukajadi Kota Pekanbaru on mediation procedure in court. Partner participation in the activities of Community Service is to provide the time, providing a place and other supporting facilities, and represents the community as participants legal counseling on increased knowledge of Kelurahan Kampung Melayu Kecamatan Sukajadi Kota Pekanbaru on mediation procedure in court. Target outcomes of Community Service activities are the publication of scientific articles in the Journal of Law Respublica, as well as part of the implementation of the Tri Dharma college. The conclusion was that community service activities have been successfully implemented and the benefits can be felt directly by the participants, namely to increase public knowledge Kelurahan Kampung Melayu Kecamatan Sukajadi Kota Pekanbaru on mediation procedure in court. It can be seen from the answers of the participants in the questionnaire given after the implementation of the activities. Of the 31 participants, 95% answered have understood. Her advice is preferably routine activities with this theme carried out in other villages so that people can know and understand about the mediation procedure in court, especially after birth of Supreme Court Regulation No. 1 Year 2016 on Procedures for Mediation in the Court.